Factors Associated with the Incidence of Measles in Toddlers (Aged 0-5 Years) in Central Jakarta in 2024 - Ely Nofiyanti; Ekowati Rahajeng; Laila Ulfa (International Journal of Health and Pharmaceutical (IJHP), 2025)
Measles remains a significant public health problem, particularly among children under five years old in urban areas. This study aimed to identify factors associated with measles incidence among children aged 0–5 years in Central Jakarta in 2024. A cross-sectional design was applied using secondary data from measles epidemiological investigations conducted by the Central Jakarta Health Sub-Department in 2024. The study included 115 children recorded in surveillance reports. Data were analyzed using univariate, bivariate, and multivariate methods with logistic regression. The results showed that several factors were associated with measles incidence, including nutritional status, age, sex, immunization history, and history of exposure. Multivariate analysis revealed that the dominant factor was nutritional status with an OR of 13.120 (95% CI: 1.698–101.320; p=0.014). In conclusion, nutritional status is the most influential factor in measles incidence among children in Central Jakarta. Efforts to improve children's nutritional status through growth monitoring, supplementation, and nutrition education should be strengthened to reduce measles risk.